Assessing environmental quality and health implications of slaughterhouses’ operation within urban residential settings of a developing country - Lateef Adeleke Adeniyi; Solomon Ayodeji Olatunji; Sikiru Akintunde Folorunso; Oluyemi Peter Adesoye (Urbanization, Sustainability and Society)
Purpose – This study aims to assess the environmental implications of slaughterhouses within residential areas of Ede, Nigeria. The effects on the health of the residents and the physical environment were examined. It provides an insight into the levels of damages done by this facility on the nearby residents and the implications on the quality of life. Design/methodology/approach – The research was based on the 16 slaughterhouses identified in the study area, which formed the sample population. From these, eight (representing 50%) were randomly chosen for survey. To determine the suitability of this facility in the current locations and its impacts on nearby residents and the immediate environment, occupants of residential structures within a range of the selected slaughterhouses were considered for investigation. Data collected were analysed using descriptive statistics. Findings – The study shows that most slaughterhouses existed earlier than many residential structures. Their owners are mainly aged people with low levels of education and income. Wastes generated from the slaughterhouses dominated by organic content were poorly handled. The results of the soil tests conducted around the slaughterhouses show that acidic content exceeds the 7Ph threshold recommended by the World Health Organisation. Most residents living in buildings within a close range are observed to have experienced high disturbances from environmental pollution, which is suspected to result to various degrees of health challenges. Originality/value – The paper builds on revealing the implications of operating slaughterhouses within residential area which is common practices in most developing countries. The effects of these operations on the environment and wellbeing of the inhabitants were revealed.